THE SURFACE WATER STORAGE PROBLEM IN ARID REGIONS: A CASE STUDY OF THE GARGAR DAM, ALGERIA - Benfetta, H.; Ouadja, A. (University of Eloued جامعة الوادي, 2017)
Most dams lose capacity as a result of three principal phenomena: leakage, sedimentation and evaporation. The study of these phenomena is particularly important as they can also endanger the damâ€™s stability. Here, we examine the case of the Gargar dam in western Algeria. This dam is located in an arid zone where water resources are becoming increasingly scarce. It is situated 5 km from the city of Ghelizane and is subject to considerable water loss. It has never been filled to capacity, and is now threatened by leakages that are clearly evolving over time. This article extends our earlier studies of the dam. Our work has estimated total average losses of 25 million m3 /year for the period 1988â€“2015, made up of leakage (0.3Â million m3 /year) and evaporation (18 million m3 /year), while dead storage accounts for 4.6 million m3 /year.Â However, total losses for 2004 were estimated at 113.9 million m3, which increased to the alarming value of 166.8 million m3 in 2015. We analyze variation in leakage as a function of the reservoir level, and quantify losses due to leaks, sedimentation and evaporation.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Gargar Dam ; Leakage; Sedimentation; Evaporation; Arid areas; Algeria.